Determinants of pre-hospital pharmacological intervention and its association with outcome in acute myocardial infarction. Issue 1 (December 2015) - Strandmark, Rasmus; Herlitz, Johan; Axelsson, Christer; Claesson, Andreas; Bremer, Anders; Karlsson, Thomas; Jimenez-Herrera, Maria; Ravn-Fischer, Annica
Abstract Background The aim of this study was a) To identify predictors of the use of aspirin in the pre-hospital setting in acute myocardial infarction (AMI) and b) To analyze whether the use of any of the recommended medications was associated with outcome. Methods All patients with a final diagnosis of AMI, transported by the Emergency Medical Services (EMS) and admitted to the coronary care unit at Sahlgrenska University Hospital in Gothenburg, Sweden, in 2009–2011, were included. Results 1, 726 patients were included. 58 % received aspirin by the EMS. Ischemic heart disease (IHD) was suspected in 84 %. Among patients who did not receive aspirin IHD was still suspected in 67 %. Among patients in whom IHD was suspected, and who were not on chronic treatment with aspirin the following predicted its pre-hospital use: a) age (odds ratio 0.98; 95 % confidence interval (CI) 0.96–0.99); b) a history of myocardial infarction (2.21; 1.21–4.04); c) priority given by EMS (8.07; 5.42–12.02); d) ST-elevation on ECG on admission to hospital (2.22; 1.50–3.29); e) oxygen saturation > 90 % (3.37; 1.81–6.27). After adjusting for confounders among patients who were not on chronic aspirin, only nitroglycerin of the recommended medications was associated with a reduced risk of death within 1 year (hazard ratio 0.40; 95 % CI 0.23–0.70). Conclusions Less than six out of ten patients with AMI received pre-hospital aspirin. Five clinical factors were independently associated with the pre-hospital administration of aspirin. This suggests that the decision to treat is multifactorial, and it highlights the lack of accurate diagnostic tools in the pre-hospital environment. Nitroglycerin was independently associated with a reduced risk of death, suggesting that we select the use for a low-risk cohort.